ANALISIS PENGARUH PENDAPATAN, LITERASI PERBANKAN SYARIAH DAN RELIGIUSITAS TERHADAP MINAT MENABUNG DI BANK SYARIAH - abdul jabbar, arroyyan; Nugroho Suryo Bintoro (Islamic Economics and finance in Focus, 2022)
This research is based on the development of Islamic economics and Islamic banking as well as students' interest in saving, especially students of the Islamic economics study program at Universitas Brawijaya at Islamic banks, where they are studying Islamic economic concepts. This study wanted to determine the effect of income, Islamic banking literacy, and religiosity on student interest in saving at Islamic banks. This study uses the theory of income, savings, banking, and religiosity. This research method is descriptive quantitative, which is a method to test certain theories that mutually test the relationship between related variables, namely the x variable (income, Islamic banking literacy and religiosity) and the y variable (student saving interest). So that these variables will be measured with research instruments so that the existing data in the form of numbers will be calculated and analyzed based on statistical procedures, namely with the SPSS calculation application. The source of the data obtained from the distribution of the questionnaire then analyzed using analytical techniques using regression analysis. The population in this study were students of the University's Islamic Economics Study Program Brawijaya class from 2017 to 2020 and the sample is 80 related students. The test results concluded that the X variable (income, Islamic banking literacy and religiosity) had a significant effect on the Y variable (student saving interest).